Estrogen Signals Through Peroxisome Proliferator-Activated Receptor−γ Coactivator 1α to Reduce Oxidative Damage Associated With Diet-Induced Fatty Liver Disease - Besse-Patin, Aurèle; Léveillé, Mélissa; Oropeza, Daniel; Nguyen, Bich N.; Prat, Annik; Estall, Jennifer L. (Gastroenterology (New York, N.Y. 1943), 2017)
Inefficient fatty acid oxidation in mitochondria and increased oxidative damage are features of non-alcoholic fatty liver disease (NAFLD). In rodent models and patients with NAFLD, hepatic expression of peroxisome proliferator-activated receptor−γ (PPARG) coactivator 1α (PPARGC1A or PGC1A) is inversely correlated with liver fat and disease severity. A common polymorphism in this gene (rs8192678, encoding Gly482Ser) has been associated with NAFLD. We investigated whether reduced expression of PGC1A contributes to development of NAFLD using mouse models, primary hepatocytes, and human cell lines. HepG2 cells were transfected with variants of PPARGC1A and protein and messenger RNA levels were measured. Mice with liver-specific hemizygous or homozygous disruption of Ppargc1a (Ppargc1af/+Alb-cre+/0 and Ppargc1af/f Alb-cre+/0 mice, respectively) were fed regular chow (control) or a high-fat diet supplemented with 30% d-fructose in drinking water (obesogenic diet) for 25–33 weeks. Liver tissues were analyzed by histology and by immunoblotting. Primary hepatocytes were analyzed for insulin signaling, reactive oxygen species, and estrogen response. Luciferase reporter expression was measured in transfected H2.35 cells expressing an estrogen receptor reporter gene, estrogen receptor 1, and/or PGC1A/B. The serine 482 variant of the human PGC1A protein had a shorter half-life than the glycine 482 variant when expressed in HepG2 cells. Liver tissues from mice with liver-specific hemizygous disruption of Ppargc1a placed on an obesogenic diet expressed increased markers of inflammation and fibrosis and decreased levels of antioxidant enzymes compared with the Ppargc1a+/+ on the same diet. Oxidative damage was observed in livers from Ppargc1af/+Alb-cre+/0 mice of each sex, in a cell-autonomous manner, but was greater in livers from the female mice. Expression of PGC1A in H2.35 cells coactivated estrogen receptor 1 and was required for estrogen-dependent expression of genes that encode antioxidant proteins. These findings could account for the increased liver damage observed in female Ppargc1af/+Alb-cre+/0 mice; while, compensatory increases in PPARG coactivator 1β could prevent oxidative damage associated with complete loss of PGC1A expression in Ppargc1af/fAlb-cre+/0 female mice. In mice, loss of estrogen signaling contributes to oxidative damage caused by low levels of PGC1A in liver, exacerbating steatohepatitis associated with diets high in fructose and fat.